Strengthening health system governance using health facility service charters: a mixed methods assessment of community experiences and perceptions in a district in Kenya. Issue 1 (June 2015) - Atela, Martin; Bakibinga, Pauline; Ettarh, Remare; Kyobutungi, Catherine; Cohn, Simon
Abstract Background Enhancing accountability in health systems is increasingly emphasised as crucial for improving the nature and quality of health service delivery worldwide and particularly in developing countries. Accountability mechanisms include, among others, health facilities committees, suggestion boxes, facility and patient charters. However, there is a dearth of information regarding the nature of and factors that influence the performance of accountability mechanisms, especially in developing countries. We examine community members' experiences of one such accountability mechanism, the health facility charter in Kericho District, Kenya. Methods A household survey was conducted in 2011 among 1, 024 respondents (36 % male, 64 % female) aged 17 years and above stratified by health facility catchment area, situated in a division in Kericho District. In addition, sixteen focus group discussions were conducted with health facility users in the four health facility catchment areas. Quantitative data were analysed through frequency distributions and cross-tabulations. Qualitative data were transcribed and analysed using a thematic approach. Results The majority (65 %) of household survey respondents had seen their local facility service charter, 84 % of whom had read the information on the charter. Of these, 83 % found the charter to be useful or very useful. According to the respondents, the charters provided useful information about the services offered and their costs, gave users a voice to curb potential overcharging and helped users plan their medical expenses before receiving the service. However, community members cited several challenges with using the charters: non-adherence to charter provisions by health workers; illegibility and language issues; lack of expenditure records; lack of time to read and understand them, often due to pressures around queuing; and socio-cultural limitations. Conclusion Findings from this study suggest that improving the compliance of health facilities in districts across Kenya with regard to the implementation of the facility service charter is critical for accountability and community satisfaction with service delivery. To improve the compliance of health facilities, attention needs to be focused on mechanisms that help enforce official guidelines, address capacity gaps, and enhance public awareness of the charters and their use.